Cyclosporine A-loaded apoferritin alleviates myocardial ischemia-reperfusion injury by simultaneously blocking ferroptosis and apoptosis of cardiomyocytes. (1st April 2023) - Qian, Wenqiang; Liu, Daozhou; Han, Ying; Liu, Miao; Liu, Bao; Ji, Qifeng; Zhang, Bangle; Mei, Qibing; Zhou, Siyuan; Cheng, Ying
Abstract: Myocardial ischemia-reperfusion injury (MI/RI) seriously restricts the therapeutic effect of reperfusion. It is demonstrated that ferroptosis and apoptosis of cardiomyocytes are widely involved in MI/RI. Therefore, simultaneous inhibition of ferroptosis and apoptosis of cardiomyocytes can be a promising strategy to treat MI/RI. Besides, transferrin receptor 1 (TfR1) is highly expressed in ischemic myocardium, and apoferritin (ApoFn) is a ligand of the transferrin receptor. In this study, CsA@ApoFn was prepared by wrapping cyclosporin A (CsA) with ApoFn and actively accumulated in ischemic cardiomyocytes through TfR1 mediated endoctosis in MI/RI mice. After entering cardiomyocytes, ApoFn in CsA@ApoFn inhibited ferroptosis of ischemic cardiomyocytes by increasing the protein expression of GPX4 and reducing the content of labile iron pool and lipid peroxides. At the same time, CsA in CsA@ApoFn attenuated the apoptosis of ischemic cardiomyocytes through recovering mitochondrial membrane potential and reducing the level of reactive oxygen species, which played a synergistic role with ApoFn in the treatment of MI/RI. In conclusion, CsA@ApoFn restored cardiac function of MI/RI mice by simultaneously blocking ferroptosis and apoptosis of cardiomyocytes. ApoFn itself not only served as a safe carrier to specifically deliver CsA to ischemic cardiomyocytes but also played a therapeutic role on MI/RI. CsA@ApoFn is proved as an effective drug delivery platform for the treatment of MI/RI. Statement of significance: Recent studies have shown that ferroptosis is an important mechanism of myocardial ischemia-reperfusion injury (MI/RI). Therefore, simultaneous inhibition of ferroptosis and apoptosis of cardiomyocytes can be a promising strategy to treat MI/RI. Apoferritin, as a delivery carrier, can actively target to ischemic myocardium through binding with highly expressed transferrin receptor on ischemic cardiomyocytes. At the same time, apoferritin plays a protective role on ischemic cardiomyocytes by inhibiting ferroptosis. This strategy of killing two birds with one stone significantly improves the therapeutic effect on MI/RI while does not need more pharmaceutical excipients, which has the prospect of clinical transformation. Graphical abstract: Image, graphical abstract